The internal sequence of the peptide-substrate determines its N-terminus trimming by ERAP1. - Irini Evnouchidou; Frank Momburg; Athanasios Papakyriakou; Angeliki Chroni; Leondios Leondiadis; Shih-Chung Chang; Alfred L Goldberg; Efstratios Stratikos (PLoS ONE)
Background Endoplasmic reticulum aminopeptidase 1 (ERAP1) trims N-terminally extended antigenic peptide precursors down to mature antigenic peptides for presentation by major histocompatibility complex (MHC) class I molecules. ERAP1 has unique properties for an aminopeptidase being able to trim peptides in vitro based on their length and the nature of their C-termini. Methodology/principal findings In an effort to better understand the molecular mechanism that ERAP1 uses to trim peptides, we systematically analyzed the enzyme's substrate preferences using collections of peptide substrates. We discovered strong internal sequence preferences of peptide N-terminus trimming by ERAP1. Preferences were only found for positively charged or hydrophobic residues resulting to trimming rate changes by up to 100 fold for single residue substitutions and more than 40,000 fold for multiple residue substitutions for peptides with identical N-termini. Molecular modelling of ERAP1 revealed a large internal cavity that carries a strong negative electrostatic potential and is large enough to accommodate peptides adjacent to the enzyme's active site. This model can readily account for the strong preference for positively charged side chains. Conclusions/significance To our knowledge no other aminopeptidase has been described to have such strong preferences for internal residues so distal to the N-terminus. Overall, our findings indicate that the internal sequence of the peptide can affect its trimming by ERAP1 as much as the peptide's length and C-terminus. We therefore propose that ERAP1 recognizes the full length of its peptide-substrate and not just the N- and C- termini. It is possible that ERAP1 trimming preferences influence the rate of generation and the composition of antigenic peptides in vivo.